Artificial Intelligence and the Tripartite Role of University Teachers - Fasanmi, Success Ayodeji; Seyama, Sadi (Studies in Learning and Teaching, 2025)
Artificial intelligence (AI) is making impact in every field of study, various aspects of human life, and the higher education sector. The functioning of the university revolves around three main functions which include teaching, research and community service. This study examined the impact of AI on the performance of the three core functions of the university teacher. The theoretical framework for the study is the connectivism theory, which is of the view that technology plays a crucial role in connecting teachers, researchers, and learners to a vast amount of information. Using the thematic review approach and available secondary data on impact of AI on teaching, research and community service, the desktop design was employed for the paper. The desktop design is concerned with cross-referencing and collection of data from existing resources such as academic publications, empirical reports and bulletins. The findings of the study established that the emergence of AI in higher education is a positive development which has made the task of teaching, research and community service easier with the various AI support tools. The study concluded by emphasizing the need for education stakeholders to use various AI tools responsibly.